2023
DOI: 10.3390/molecules28124665
|View full text |Cite
|
Sign up to set email alerts
|

Vincamine Ameliorates Epithelial-Mesenchymal Transition in Bleomycin-Induced Pulmonary Fibrosis in Rats; Targeting TGF-β/MAPK/Snai1 Pathway

Abstract: Idiopathic pulmonary fibrosis is a progressive, irreversible lung disease that leads to respiratory failure and death. Vincamine is an indole alkaloid obtained from the leaves of Vinca minor and acts as a vasodilator. The present study aims to investigate the protective activity of vincamine against EMT in bleomycin (BLM)-induced pulmonary fibrosis via assessing the apoptotic and TGF-β1/p38 MAPK/ERK1/2 signaling pathways. In bronchoalveolar lavage fluid, protein content, total cell count, and LDH activity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
3
3
0
Order By: Relevance
“…These results are in agreement with previous studies. 28,29 Moreover, LDH activity in BALF was increased in BLM rats indicating interstitial lung injury, which is in line with previous studies. 29,30 Surprisingly, BET revealed an anti-inflammatory effect emphasized by attenuating total and differential cell counts (neutrophils and lymphocytes counts) and LDH activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in agreement with previous studies. 28,29 Moreover, LDH activity in BALF was increased in BLM rats indicating interstitial lung injury, which is in line with previous studies. 29,30 Surprisingly, BET revealed an anti-inflammatory effect emphasized by attenuating total and differential cell counts (neutrophils and lymphocytes counts) and LDH activity.…”
Section: Discussionsupporting
confidence: 90%
“…28,29 Moreover, LDH activity in BALF was increased in BLM rats indicating interstitial lung injury, which is in line with previous studies. 29,30 Surprisingly, BET revealed an anti-inflammatory effect emphasized by attenuating total and differential cell counts (neutrophils and lymphocytes counts) and LDH activity. This is in harmony with the reported anti-inflammatory effect of BET in lipopolysaccharide-induced acute lung injury in mice.…”
Section: Discussionsupporting
confidence: 90%
“…It disclaimed that an elevation in ROS generates sepsispersuaded kidney damage by decreasing the host's anti-oxidant defense mechanisms, leading to cell damage 51,53 . www.nature.com/scientificreports/ Numerous pro-inflammatory and pro-fibrotic signaling networks, including TGF-β1, NF-κB, p53, and MAPK family members, are activated more strongly by ROS and oxidative stress [53][54][55][56] . It was implicated that TGF-β1 has a crucial function in generating EMT and is the driver of kidney fibrogenesis through TGF-β1/Smad/p53 signaling pathways [57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pro-inflammatory and pro-fibrotic signaling networks, including TGF-β1, NF-κB, p53, and MAPK family members, are activated more strongly by ROS and oxidative stress 53 56 . It was implicated that TGF-β1 has a crucial function in generating EMT and is the driver of kidney fibrogenesis through TGF-β1/Smad/p53 signaling pathways 57 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo models of IPF induced by bleomycin, a chemotherapeutic agent known to cause pulmonary fibrosis via ROS production, have shown a significant reduction in GPX levels in treated groups compared to controls [ 124 , 125 ]. Research by Zeng et al indicated that GPX3 expression is downregulated in the lung tissues of IPF patients, leading to increased oxidative stress and exacerbating the fibrotic phenotype [ 126 ].…”
Section: Research Progress In Gpx3 and Non-neoplastic Diseasesmentioning
confidence: 99%